Makna dan Representasi Fenomena FOMO dalam Tren Hijab Turban di Media Sosial TikTok bagi Mahasiswa Ilmu Komunikasi UIN Raden Fatah - Lestari, Selfi; Bernolian, Dion; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to examine the meaning and representation of the Fear of Missing Out (FOMO) phenomenon in the hijab turban trend on TikTok among Communication Studies students at UIN Raden Fatah. FOMO, a psychological condition where individuals feel anxious about being left out of popular trends, plays a significant role in influencing participation in digital trends. The hijab turban trend, which combines religious, cultural, and fashion elements, has become a prominent focus on TikTok, especially among Muslim women, including university students. Through a qualitative approach, this research explores how FOMO affects students' decision to follow the hijab turban trend and how the trend is represented in TikTok content. Interviews were conducted with students who actively engage in social media, revealing insights into the pressure to conform to digital trends, the role of social validation, and the influence of influencers and TikTok's algorithm in shaping fashion choices. The findings indicate that while the hijab turban represents a modern expression of identity, it also raises concerns about the commercialization of religious symbols and the psychological pressure to align with societal standards.